Open Pedagogy through Community-Directed, Student-led partnerships: Establishing CURE (Community-University Research Exchange) at Temple University Libraries - Urooj Nizami; Adam Shambaugh (Open Praxis, 2019)
This paper reports on the establishment of an open pedagogy initiative between community organisations and students, facilitated by the Temple University Libraries (TUL) and faculty in the Philadelphia area. The Community-University Research Exchange (CURE) produces community-driven social justice research. Library facilitators solicit research questions and project proposals from grassroots community organisations who experience social and economic marginalisation, limiting or even disallowing the access to information that is vital to innovating the services organisations provide. Students select from a bank of research projects, developed by community organisations, identifying issues that they wish to investigate, skillsets they hope to master, or organisations for whom they hope to contribute their intellectual labour. This project facilitates community organisations’ direction and autonomy in promoting beneficial research objectives. It also foregrounds students as the directors of their own knowledge output and learning. This project is modeled after the Quebec Public Interest Research Group’s (QPIRG) programme.